2015
DOI: 10.3189/2015jog14j157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CryoSat-2 derived sea-ice freeboard over fast ice in McMurdo Sound, Antarctica

Abstract: ABSTRACT. Using in situ data from 2011 and 2013, we evaluate the ability of CryoSat-2 (CS-2) to retrieve sea-ice freeboard over fast ice in McMurdo Sound. This provides the first systematic validation of CS-2 in the coastal Antarctic and offers insight into the assumptions currently used to process CS-2 data. European Space Agency Level 2 (ESAL2) data are compared with results of a Waveform Fitting (WfF) procedure and a Threshold-First-Maximum-Retracker-Algorithm employed at 40% (TFMRA40). A supervised freeboa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…In their study they could show that the winter mean freeboard from ERS-2 shows a reasonable distribution and good qualitative agreement with ship-based observations. Later, Price et al (2015) found a good agreement with field data using CS-2 radar signals to derive sea-ice freeboard over the fast ice of McMurdo Sound.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In their study they could show that the winter mean freeboard from ERS-2 shows a reasonable distribution and good qualitative agreement with ship-based observations. Later, Price et al (2015) found a good agreement with field data using CS-2 radar signals to derive sea-ice freeboard over the fast ice of McMurdo Sound.…”
Section: Introductionsupporting
confidence: 54%
“…A study of Price et al (2015) indicated that the reflection horizon of CS-2 data over Antarctic sea ice, derived with a retracker threshold of 40 %, is certainly close to the snow/air interface. However, Operation IceBridge laser freeboard measurements over Antarctic sea ice as well as laser altimeter data from the R/V Polarstern expedition PS81 in winter 2013 and PS89 in summer 2014/2015 are expected to be available in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser and radar altimetries are the most effective methods to date and have produced the first sea‐ice thickness results over the Antarctic and WG (Giles et al, ; Kurtz & Markus, ; Yi et al, ; Zwally et al, ). However, altimetric sea‐ice thickness retrievals are subject to large uncertainties, particularly due to the unknown thickness and microwave scattering properties of the overlying snow (e.g., D. Price et al, ; Xie et al, ). These uncertainties are further complicated by the snow‐ice interface, which can fall below the local water level as a result of heavy snow fall on the relatively thin sea ice, causing a negative freeboard and widespread flooding (e.g., Massom et al, ).…”
Section: Cryosphere Ii: Sea Icementioning
confidence: 99%
“…For CryoSat the assumption is that most of the signal is scattered at the snow-ice interface; however different studies suggest that in some cases (e.g. with a saline snowpack, slush and layering) the main scattering horizon is rather "somewhere within the snowpack" (King et al, 2018;Price et al, 2015;Kwok and Kacimi, 2018). Alexandrov et al (2010) state that the freeboard error may be reduced by averaging.…”
Section: Rmsementioning
confidence: 99%